He wil eat a total of 55.2 hot dogs. there 60 seconds in a minute . he plans to eat 1 hotdog in every 13 seconds . you divide 60 by 13 . he will eat 4.6 hot dogs in a minute . then you multiply 4.6 by 12.
Answer:
-21
Step-by-step explanation:
We are told to find f(x) + g(x) for x= -3. Therefore, we must evaluate f(-3) and g(-3), then add them together.
First, evaluate f(-3).
f(x)=4x-7
To find f(-3), we need to substitute -3 in for x.
f(-3)= 4(-3)-7
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction First, multiply 4 and -3.
f(-3)= -12-7
Next, subtract 7 from -12
f(-3)= -19
Next, find g(-3).
g(x)=2x+4
To find g(-3), substitute -3 in for x.
g(-3)= 2(-3)+4
Solve according to PEMDAS. First, multiply 2 and -3.
g(-3)= -6+4
Next, add -6 and 4
g(-3)= -2
Now, we can add f(-3) and g(-3) together.
f(-3) + g(-3)
f(-3)= -19
g(-3)= -2
-19 + -2
Add
-21
.03*.03=.009 .009*.03=.000027 so the answer is .000027
Answer:
Always true because there are no other options that allow the equations to be true
Step-by-step explanation:
a+4=8
subtract 4
a=4
4-m=2
add m
4=2+m
subtract 2
2=m